Mother Goose on Parade - Virginia Ballaseyus::::::::: (Sam Fox Pub. Co.)
Piano and vocal score, 5 p. On cover: Dedicated to the Golden Gate Amusement Company, sponsors of the Childrens Village On p.[2]: especially written for the Childrens Village of the Golden Gate International Exposition 1939 Publishers advertisement on verso of last leaf.